2005
DOI: 10.1103/physrevlett.95.162701
|View full text |Cite
|
Sign up to set email alerts
|

Fast Decision in Favor of the Slow Fission Process

Abstract: The fission probability P f of highly excited targetlike nuclei produced in reactions of 2.5 GeV protons on Au, Bi, and U was studied as a function of excitation energy E whereby E is deduced eventwise from the multiplicity of evaporated light particles. At the highest E of 1000 MeV P f amounts to 30% with all 3 target nuclei irrespective of the initial fissility. Statistical-model calculations satisfactorily reproduce the observed evolution of P f with E -provided that no extra transient delay is introduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 16 publications
5
32
2
Order By: Relevance
“…For proton and α emission, the combination of binding energy and emission barrier decides whether τ ssc increases or decreases with Z ssc . The result also indicated that the pre-saddle time is less than 2 zs which is in agreement with the conclusion of recent fission time-scale measurements using the fission probability probe [19,20].…”
Section: Results From Neutron Proton and α-Particle Clocksupporting
confidence: 90%
See 1 more Smart Citation
“…For proton and α emission, the combination of binding energy and emission barrier decides whether τ ssc increases or decreases with Z ssc . The result also indicated that the pre-saddle time is less than 2 zs which is in agreement with the conclusion of recent fission time-scale measurements using the fission probability probe [19,20].…”
Section: Results From Neutron Proton and α-Particle Clocksupporting
confidence: 90%
“…Fission lifetime can be measured using direct methods like crystal blocking technique [14], K-vacancy production [15] and indirect methods like neutron clock [1,12], light charged particle clock [1,16], GDR clock [2,10], evaporation residues (ER) corss-section [2,17,18] and fission probabilities [19,20]. Early measurements [10,12] using the neutron and GDR clocks showed that the fission time-scales were much larger than those predicted by the standard statistical model.…”
Section: Introductionmentioning
confidence: 99%
“…3). Our results nicely agree with the non-Gaussian low-energy tailing observed by Tischenko et al [5], confirmed also by Mutterer et al [6]. …”
Section: Binary Fissionsupporting
confidence: 93%
“…[27,28,29]. The present work goes a step further by utilising for the first time highly fissile spherical systems for which fission properties can be studied over a much wider range of excitation energy.…”
mentioning
confidence: 99%